A very potent factor V inhibitor interferes with the levels of all coagulation factors and causes a fatal hemorrhagic syndrome. (28th May 2019) - Hoffmann, Claire; Amiral, Jean; Rezig, Schéhérazade; Kerspern, Hélène; Jantzem, Hélène; Robin, Sara; Collins, Adam; Mornet, Clelia; Mingant, Fanny; Pan Petesch, Brigitte; Ianotto, Jean‐Christophe; Lippert, Eric; et al.
Abstract: We report a very high factor V inhibitor affecting the measurement of all coagulation factors besides fibrinogen, all these factors being dramatically decreased. This inhibitor could be linked to antibiotic use. The patient died of massive hemorrhage before a plasma exchange could be initiated.